2013
DOI: 10.1016/j.ajhg.2013.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide Association Analysis of Blood-Pressure Traits in African-Ancestry Individuals Reveals Common Associated Genes in African and Non-African Populations

Abstract: High blood pressure (BP) is more prevalent and contributes to more severe manifestations of cardiovascular disease (CVD) in African Americans than in any other United States ethnic group. Several small African-ancestry (AA) BP genome-wide association studies (GWASs) have been published, but their findings have failed to replicate to date. We report on a large AA BP GWAS meta-analysis that includes 29,378 individuals from 19 discovery cohorts and subsequent replication in additional samples of AA (n = 10,386), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
182
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 187 publications
(198 citation statements)
references
References 41 publications
14
182
1
1
Order By: Relevance
“…In contrast, for a variety of complex traits studied to date, accumulating evidence suggests considerable numbers of overlap loci between ethnicities. [30][31][32][33] For these traits, a large proportion of SNPs selected based on a large European GWAS are expected to be relevant in non-European populations. Therefore, a set selected based on a large GWAS in a non-matching population is expected to harbor higher fraction of variants for the target population than a set selected on a small dataset in matching population.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, for a variety of complex traits studied to date, accumulating evidence suggests considerable numbers of overlap loci between ethnicities. [30][31][32][33] For these traits, a large proportion of SNPs selected based on a large European GWAS are expected to be relevant in non-European populations. Therefore, a set selected based on a large GWAS in a non-matching population is expected to harbor higher fraction of variants for the target population than a set selected on a small dataset in matching population.…”
Section: Discussionmentioning
confidence: 99%
“…Among these 11 Rho-GEFs, GEF-H1, LARG and p190RhoGEF are RhoA-targeting GEFs that are involved in integrin-mediated mechanotransduction at focal adhesions (Lim et al, 2008;Tomar and Schlaepfer, 2009;Guilluy et al, 2011). In addition, single-nucleotide polymorphism analysis revealed that the genes encoding ARHGEF10 and PLEKHG1 are associated with atherothrombotic stroke and high blood pressure traits, respectively (Matsushita et al, 2010;Franceschini et al, 2013), suggesting that they have roles in blood vessel homeostasis and functions. However, little is known about the regulation mechanisms and functional roles of these Rho-GEFs in mechanotransduction in vascular endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 Genome-wide association studies (GWAS) have identified multiple single nucleotide polymorphisms (SNPs) associated with blood pressure (BP). [3][4][5][6][7][8][9] Genetic risk scores (GRSs) based on those genetic variants identified in European populations were reported to be associated with incident hypertension and cardiovascular events. tobacco use, which affect the variability of BP.…”
mentioning
confidence: 99%